A Clinical and Pathological Overview of Vulvar Condyloma Acuminatum, Intraepithelial Neoplasia, and Squamous Cell Carcinoma. (25th February 2014) - Léonard, Boris; Kridelka, Frederic; Delbecque, Katty; Goffin, Frederic; Demoulin, Stéphanie; Doyen, Jean; Delvenne, Philippe
Abstract : Condyloma acuminatum, intraepithelial neoplasia, and squamous cell carcinoma are three relatively frequent vulvar lesions. Condyloma acuminatum is induced by low risk genotypes of human papillomavirus (HPV). Vulvar intraepithelial neoplasia (VIN) and squamous cell carcinoma have different etiopathogenic pathways and are related or not with high risk HPV types. The goal of this paper is to review the main pathological and clinical features of these lesions. A special attention has been paid also to epidemiological data, pathological classification, and clinical implications of these diseases.